2018
DOI: 10.1126/scisignal.aao4006
|View full text |Cite
|
Sign up to set email alerts
|

The receptor tyrosine kinase TrkB signals without dimerization at the plasma membrane

Abstract: Tropomyosin-related tyrosine kinase B (TrkB) is the receptor for brain-derived neurotrophic factor (BDNF) and provides critical signaling that supports the development and function of the mammalian nervous system. Like other receptor tyrosine kinases (RTKs), TrkB is thought to signal as a dimer. Using cell imaging and biochemical assays, we found that TrkB acted as a monomeric receptor at the plasma membrane regardless of its binding to BDNF and initial activation. Dimerization occurred only after the internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
2
22
2
Order By: Relevance
“…Our model contrasts with the model of TrkB activation recently proposed (46). In that model TrkB is activated by its ligand BDNF and signal in a monomeric state and only after internalization in the endosomes forms dimers (46). Interestingly, and in favor of our model, using the same methodology the authors found that TrkA form dimers with NGF at the plasma membrane.…”
Section: Discussioncontrasting
confidence: 84%
“…Our model contrasts with the model of TrkB activation recently proposed (46). In that model TrkB is activated by its ligand BDNF and signal in a monomeric state and only after internalization in the endosomes forms dimers (46). Interestingly, and in favor of our model, using the same methodology the authors found that TrkA form dimers with NGF at the plasma membrane.…”
Section: Discussioncontrasting
confidence: 84%
“…In neurons in particular, endosomes take on an additional signaling role. Their rapid retrograde transport serves as an efficient mechanism for signal transduction across large distances (i.e., neurotrophin transport from the distal synapse to the cell body; Howe and Mobley, 2004 ), or a mechanism to regulate the nature and intensity of a signal (Zahavi et al, 2018 ). A link between endosomal trafficking and RNA silencing was first established when the RISC components Ago2 and GW182 were found to be enriched in their fraction of multivesicular bodies (MVBs), suggesting that these foci are distinct from P-bodies (Gibbings et al, 2009 ; Siomi and Siomi, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…TrkB agonists can differentially activate selective downstream pathways, and TrkB-PLCÎł1 activation is complex. This concept is already evident in recent literature that has shown evidence of TrkB receptor activation and signaling without dimerization, suggesting that TrkB can under certain conditions exist and function as a monomeric receptor at the plasma membrane ( 75 ). Moreover, recent studies examining plasma membrane diffusion kinetics have demonstrated that up to 20% of the Trk family may exist as dimers or oligomers prior to neurotrophin binding ( 76 ), though their function remains a topic of debate ( 77 ).…”
Section: Discussionmentioning
confidence: 76%